Degradation mechanism of stainless steel by U-Zr-O molten mixture during core degradation of BWR severe accident. Issue 6 (3rd June 2021) - Itoh, Ayumi; Andrews, Nathan C.; Luxat, David L.; Gauntt, Randall O.; Kurata, Masaki; Kobayashi, Yoshinao
ABSTRACT: Degradation mechanism involving the interaction between the U-Zr-O phase from molten fuel cladding and steel was investigated at the lower structure of core region of the boiling water reactor, which could take place at low temperatures compared to the failure conditions typically assumed in the current severe accident codes. The non-isothermal interaction was simulated by the heat and mass transport equations with possible chemical reactions estimated by thermodynamic database and the following potential mechanisms were identified: (1) the U-Zr-O melt dissolves steel leading to serious damage, (2) the reaction results in partial solidification of U-Zr-O melt near the reaction surface forming (U, Zr)O2-x phase and U-Fe-rich metallic phase and (3) unsolidified U-Zr-O melt could drain to the lower plenum through the lower structure of core support plate. These mechanisms will propose new hypothesis in which the timing of core support plate degradation could get earlier due to liquefaction of U-Fe-rich metallic phase or the timing of lower head failure of the reactor pressure vessel could be affected by drained U-Zr-O melt.